Scrolling to Success: A Systematic Analysis of Social Media’s Role in Scholarly Communications - Nur Syazwani Ahmad; Ali Fauzi; Samsul Farid Samsuddin; Shamshul Bahri (IEEE Access)
This study presents the first comprehensive systematic literature review examining the patterns and trends of social media use among Asian scholars for scholarly communication and the advancement of digital scholarship. While social media platforms have become integral to global scholarly activities, including collaboration, research dissemination, and public discourse, a thorough understanding of their specific adoption and impact within diverse Asian academic contexts has been notably absent. Through a rigorous analysis of 42 articles, selected from an initial pool of 108 publications across two major databases spanning a 14-year period, this research identifies five key themes that shape scholarly social media engagement in Asia: overall usage, analytical approaches to social media data, the functions platforms serve, the features utilized, and the communication behaviors exhibited. The synthesis of these findings reveals significant variations in how scholars across different Asian regions leverage social media for academic purposes. This pioneering review offers a structured framework for understanding digital scholarship practices within Asia, thereby highlighting critical research gaps and providing strategic directions for enhancing scholarly communication through these rapidly evolving platforms. The principal contribution of this work is the proposal of an evidence-based framework that integrates these five identified themes, establishing a novel and foundational resource for future research aimed at optimizing academic knowledge dissemination via social media in the Asian context.